Discourse of Middle Way in Islamic Jurisprudence on Career Women in Achieving The Sakinah Family: Reconstruction of Roles and Women's Identity - Danu Aris Setiyanto (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2020)
The focus of this paper is on the problems of career women, both historically and juridical. This paper tries to reconcile the longstanding debate about the role of women in the public sphere. The stigma of women being identical to the domestic duties as servants of parents or servants of husbands has begun to change in the millennial era. Women have started going out and getting a profession in various fields. This study examines textually and historically related to women and juridical reviews in classical jurisprudence and related to the Indonesian laws. This paper begins by analyzing women's position historically to analyze the development of women’s role in their life. While the juridical study by analyzing both the Marriage Law and the opinions of some fiqh experts and various other studies by the theme. This study concludes that there are career women who are challenges and at the same time opportunities to create a confident family. Progressive interpretation of career women seeks to produce fiqh in the middle way that women also have the right to do good deeds (work). However, the right given must still be based on the benefit of individuals and collectives (sakinah family).